Electrochemical Degradation of Reactive Yellow 160 Dye in Real Wastewater Using C/PbO2-, Pb + Sn/PbO2 + SnO2-, and Pb/PbO2 Modified Electrodes - Mohamed Gaber; Nasser Abu Ghalwa; Abdalla M. Khedr; Munther F. Salem (Journal of Chemistry)
Three modified electrodes (C/PbO2, Pb + Sn/PbO2 + SnO2, and Pb/PbO2) were prepared by electrodeposition and used as anodes for electrochemical degradation of Reactive Yellow 160 (RY160) dye in aqueous solution. Different operating conditions and factors affecting the treatment process including current density, temperature, initial concentration of (RY160), pH, conductive electrolyte and time of electrolysis were studied and optimized. The best degradation occurred in the presence of NaCl (4 g L−1) as a conductive electrolyte. After 15 min, nearly complete degradation of RY160 was achieved (97.9%, 96.65 and 95.35% using C/PbO2, Pb+Sn/PbO2+SnO2, and Pb/PbO2 electrodes, resp.) at pH 7.13. Higher degradation efficiency was obtained at 25°C. The optimum current density for the degradation of RY160 on all electrodes was 50 mA cm−2. The prepared C/PbO2, Pb+Sn/PbO2+SnO2 and Pb/PbO2 electrodes were found to be highly efficient in the treatment of effluents obtained from dyeing factory which contain RY160 dye with very slight matrix effect.